Knowledge, attitude and practice about osteoporosis in south-western Saudi Arabia: a cross-sectional survey. Issue 1 (2nd January 2019) - Tripathi, Rina; Makeen, Hafiz A.; Albarraq, Ahmed A.; Meraya, Abdulkarim M.; Tripathi, Pankaj; Faroug, Hana; Ibrahim, Shairien
ABSTRACT: Background : Osteoporosis is a major health problem in most nations, including Saudi Arabia. Awareness among the Saudi population is essential for early detection, timely treatment and subsequent fracture prevention. Aim : The current study was intended to evaluate the level of knowledge, attitudes and practices towards osteoporosis among the general population residing in Jazan region, south-western Saudi Arabia. Study design : A community-based cross-sectional survey was developed, and a structured questionnaire was distributed among residents of Jazan. Data were collected from 400 male and female participants and analysed using STATA 15.0 software. Results : The data revealed that most of the participants were aware about osteoporosis risks, causes and symptoms. However, knowledge and attitude levels were significantly higher among females and individuals who were <30 years of age. Likewise, knowledge and positive attitude levels were higher among graduates compared to lower education groups. Almost 69.3% of participants were aware of women's susceptibility towards osteoporosis as compared to men. Most of the participants showed a positive and advisable attitude towards osteoporosis. The practice of osteoporosis-related prevention was found to be very poor, but intake of calcium- and vitamin-rich food was found to be better among participants. Conclusion : An appreciable level of knowledge and positive attitudes towards osteoporosis was observed; however, practices for osteoporosis prevention still need improvement. The obvious gap between the osteoporosis prevention-related knowledge and practice requires innovative strategies based on local evidence to promote and encourage adoption and practice of personal protective measures.